2010
DOI: 10.1177/1753193409359493
|View full text |Cite
|
Sign up to set email alerts
|

Pins and Rubber Traction System for Intra-Articular Proximal Interphalangeal Joint Fractures Revisited

Abstract: The Pins and Rubber Traction System (PRTS) can be used to treat proximal interphalangeal intra-articular fractures. Our experience is that outcomes are not always excellent and that many patients have reduced joint function or residual deformities. The aim of this study was to evaluate the reasons behind the poorer outcomes of some of the patients treated with this system. A retrospective clinical and radiological evaluation was performed on 15 patients after a minimum of 2 years' follow-up. The mean interphal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
1
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 20 publications
5
31
1
3
Order By: Relevance
“…We found that the volar lip fractures were most frequent, which are in agreement with previously published papers [12,13]. Most fractures occurred during sports and men were more predominately injured (male:female ratio of 1.8) [5,12,[14][15][16]. The ring and little fingers were most often injured; probably since they are vulnerable as the outermost fingers and have extra mobility between the metacarpals [12,[15][16][17].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that the volar lip fractures were most frequent, which are in agreement with previously published papers [12,13]. Most fractures occurred during sports and men were more predominately injured (male:female ratio of 1.8) [5,12,[14][15][16]. The ring and little fingers were most often injured; probably since they are vulnerable as the outermost fingers and have extra mobility between the metacarpals [12,[15][16][17].…”
Section: Discussionsupporting
confidence: 91%
“…Radiological signs of posttraumatic osteoarthritis were found in 61%, where all three dorsal lip fractures showed signs of posttraumatic osteoarthritis. Arthrodesis or PIP joint prosthesis was rare, which is also the experience of other authors [6,13,16]. However, although 61% (25/41) showed radiological signs of osteoarthritis, the results from the subjective evaluation showed that most patients did not suffer from symptoms of osteoarthritis (i.e.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…15) Additionally the system allows more precise wire placement and more reproducible results. 16) Other recent studies on the Ligamentotaxor have reported similar results with average ROM at the PIPJ of up to 73°. 15) This is alongside improved grip strengths and DASH scores.…”
Section: Discussionsupporting
confidence: 61%